Silicon-based Clathrates: Potential materials for energy conversion applications. - MAHAMMEDI, Ahmed Nassim; FERHAT, Marhoun (Université de Laghouat , Bibliothèque centrale, 2018)
The most abundant element on earth after oxygen (27.6%), Silicon is certainly the basic material that has helped propel humanity from the age of steam to the era of information technology and communication. Indeed, it is not an exaggeration to note that silicon is not only the most fundamental material to study, but it is also the material found in virtually all high tech applications beginning with microelectronics (more recently nanoelectronics), thermoelectric conversion of energy, magnetic materials, sensors, micro and nano electromechanical systems as well as photovoltaic energy conversion. In this context, the direct conversion of solar energy into electricity is obviously the technology that holds the most potential for the overall coverage of future energy needs. However, the current technology (mainly Si-based) has not yet reached the efficiency of efficiency or the reduction of costs necessary for its adoption as a public product. However, silicon is still the most successful material for solar cell manufacturing, not only because of its abundance and intrinsic physical characteristics, but also because of the sharp mastery of its technology-based manufacturing technology. Microelectronics already very mature. It should be noted that the low conversion efficiency of silicon is basically due to its indirect gap, thus emphasizing the importance of the atomic arrangement of atoms in the crystal lattice. The purpose of this subject is essentially based on the modification of the crystalline structure of silicon at the atomic scale by the synthesis of new forms of silicon commonly called clathrates having cage structures similar to those of fullerenes. The experimental work will be supported by theoretical studies using ab-initio calculations as part of the functional density.